Factors Influencing Acceptance of Online Mobile Games in India - Alok Singh (International Journal of Advanced Science and Technology, 2020)
India is moving leaps and bounds to witness a surge in the number of people who are now getting connected digitally. It seems that digital is the path to trans- formation and its application to various fields is quite evident. One of the areas that is witnessing exponential growth is online gaming. This research was carried out to find out the major factors that are influencing the acceptance of online mobile games. This paper will help to identify the thought process of the consumer which has led to such growth. The online gaming industry is getting increasingly competitive and major gaming platforms as well as game developers and this paper will help them to work on the major factors to improve their positioning and strength in the industry. Data was collected from respondents by means of an online questionnaire. The importance of the factors was assessed on a Likert scale. By using statistical analysis, the study determined the importance and relevance of each factor.